New species of plume moths (Lepidoptera: Pterophoridae) from Colombia - Kovtunovich, Vasiliy N.; Ustjuzhanin, Peter Ya; Sinyaev, V. V.; Streltzov, Alexander N. (Russian entomological journal)
The article describes five new plume moths species from Colombia: Platyptilia yakovlevi Kovtunovich et Ustjuzhanin sp.n., Amblyptilia natali Kovtunovich et Ustjuzhanin sp.n., Lioptilodes arcabuco Kovtunovich et Ustjuzhanin sp.n., Hellinsia sofi Kovtunovich et Ustjuzhanin sp.n., Hellinsia staskalnoii Kovtunovich et Ustjuzhanin sp.n. For Hellinsia ochricostatus (Zeller, 1877), the female genitalia are described for the first time.